Penerapan Virgin Coconut Oil (VCO) pada Ibu Post Partum Spontan di Praktik Mandiri Bidan Lestari - Sendha Maulana; Sri Hartutik (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: According to (WHO) in 2020, there were 2.7 million cases of perineal rupture in mothers giving birth, it is estimated that this will reach 6.3 million in 2050.Childbirth and the postpartum period are processes that are vulnerable to various complications that can endanger the mother. Vaginal delivery will be more susceptible to tearing of the perineum to varying degrees. Virgin Coconut Oil (VCO is rich in vitamin E which plays a role in cell retention mechanisms in cell organs which significantly increases the activity of antioxidant enzymes. Objective: to determine changes in wound healing before and after being given Virgin Coconut Oil (VCO) Method: This application uses a case study method. This method with application to 2 respondents,given Virgin Coconut Oil (VCO) applied 3 times/day for 5 consecutive days. Results: After applying Virgin Coconut Oil (VCO) for 5 consecutive days, the result was a decrease in the rate of wound healing in both respondents. decrease in score for Mrs. F 0 (good wound healing) and Mrs. Conclusion: There were changes and differences in the level of wound healing before and after administering Virgin Coconut Oil (VCO) to the two respondents.